Know the impact of Liquid Waste Disposal Water Quality River Tarai district of Kampar Regency Mines - Nurmasadi Kurniawan; Budijono '; M. Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted in May 2013 in the waters of River TaraiDistrict of Kampar Regency Mines. While the analysis of parameters of BOD,COD, TSS and ammonia performed at the Laboratory of the Department of PublicWorks, Pekanbaru. This study aims to determine the impact of the disposal ofliquid waste on water quality River Village Tarai Tarai district of KamparRegency Mines aspects of physics (pH, temperature, flow velocity, TSS, depth)and chemical (DO, BOD, COD, Ammonia. From the research this can beconcluded that, wastewater effluent know an impact on the physical and chemicalquality of river water Tarai as TSS increased, the depth and speed of flow, BOD,COD, pH and NH3. overall impact of discharges liquid waste into the waters ofriver Tarai still not exceed the assimilation capacity of the river Tarai based on theavailability of dissolved oxygen conditions which still meets or is above theminimum requirement of fish life, which is 3 mg /l.Keywords: Liquid waste to know, the river waters tarai